The Application of Educational Game Media in Mathematics Learning for Elementary School - Suci Rahma Putri; Kartika Putri Wulan Ramadhani; Feby Kharisna (Lembaga Penerbitan dan Publikasi Ilmiah Yayasan Pendidikan Tumpuan Bangsa, 2025)
This research is motivated by the low mathematics learning outcomes of students, which are caused by the use of conventional teaching methods and the lack of engaging and interactive learning media. The aim of this study is to determine the effect of applying educational game media on the mathematical concept comprehension skills of third-grade students at SDN 16 Koto Baru. This study uses a quantitative approach with a quasi-experimental design, employing a nonequivalent control group design. The sample for this study consists of third-grade students from classes III A and III B at SD Negeri 16 Koto Baru, totaling 30 students 15 students in the experimental class and 15 students in the control class selected using a saturated sampling technique. Data collection was done using tests (pretest and posttest) with 10 multiple-choice questions. Data analysis included normality tests and hypothesis testing using an independent samples t-test with the assistance of SPSS 20. The analysis results showed a significance value of 0.242 < 0.05, indicating a difference in the improvement of mathematics learning outcomes between those using educational game media and conventional methods. Thus, it can be concluded that the use of educational game media can improve the mathematics learning outcomes of third-grade students at SDN 16 Koto Baru.